Electric power transfer concept for improved performance of multi-spool turbofan jet engine - Balaghi Enalou, Hossein (2020)
Twin spool high-bypass turbofan engines are the dominant sources of propulsion for most civil aircraft. The shaft speeds in these engines are thermodynamically coupled even with no mechanical link between them. This coupling effect results in inevitable limitations on the engine design and performance, including mismatches in the performance of the compressors at low-speed conditions, that push for undesirable air bleeding requirements. Therefore, decoupling the shaft speeds can introduce remarkable improvements to engine performance, which leads to better fuel efficiency and hence reduced emissions. A combination of solutions can offer new opportunities to address the mentioned coupling issue. These include the design trends towards the More Electric Engine (MEE) for the More Electric Aircraft (MEA), the boost in power electronics application, and introduction of new onboard Electric Power Systems (EPS) architectural paradigms. A multi-spool MEE can be equipped with an electrical machine connected to each of its shafts, which are connected via power electronics sharing a common high-voltage DC bus architecture. It is then possible to establish an “electrical bridge” to circulate the desired amount of power between the engine shafts, in order to decouple their speeds. This PhD research investigates the impact of the Electric Power Transfer (EPT) on the engine performance and introduces novel EPT-Adopted Designs (EPTAD) for the future MEA engines.